2020
DOI: 10.1002/em.22363
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of urinary bladder cancer cell proliferation by silibinin

Abstract: Silibinin, a natural compound extracted from milk thistle, has demonstrated antitumor properties in urinary bladder cancer cells; however, the role of TP53 gene in these effects is unclear. In order to better understand the molecular and antiproliferative mechanisms of this compound, urinary bladder cancer cells with different TP53 gene status, RT4 (low-grade tumor, wild TP53 gene), 5637 (high-grade tumor, Grade 2, mutated TP53 gene), and T24 (high-grade tumor, Grade 3, mutated TP53 gene) were treated with sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Moreover, SIL treatment decreased the growth and invasiveness of renal cancer 786-O cell while restraining the growth of cell and inducing program cell death in cancer Caki-1 cells through prevention of EGF, ERK1/2 (Raina et al, 2016). In accordance with these findings, several studies have demonstrated the growth inhibitory effects SIL in rat models of urinary bladder cancer, associated with elevated levels of p53 expression, phosphorylation of ERK1/2 and phospho-p65, as well as downregulation of survivin, cyclin D1 (Barros et al, 2020). The use of Sil in breast cancer cells has caused cell apoptosis in MDA-MB-231 and MCF-7 cells, which synergized with inhibition of metastasis through several proteins including insulin growth factor receptor (Si et al, 2020).…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, SIL treatment decreased the growth and invasiveness of renal cancer 786-O cell while restraining the growth of cell and inducing program cell death in cancer Caki-1 cells through prevention of EGF, ERK1/2 (Raina et al, 2016). In accordance with these findings, several studies have demonstrated the growth inhibitory effects SIL in rat models of urinary bladder cancer, associated with elevated levels of p53 expression, phosphorylation of ERK1/2 and phospho-p65, as well as downregulation of survivin, cyclin D1 (Barros et al, 2020). The use of Sil in breast cancer cells has caused cell apoptosis in MDA-MB-231 and MCF-7 cells, which synergized with inhibition of metastasis through several proteins including insulin growth factor receptor (Si et al, 2020).…”
Section: Discussionsupporting
confidence: 67%
“…[27][28][29] TGF-β/Smad signaling plays a key role in the epithelial-mesenchymal transition pathway and carcinogenesis in many cancer types. [30][31][32] Results show TGF-β/Smad signaling was activated by RRBP1 overexpression. Therefore, these data indicated that RRBP1 overexpression promoted cell proliferation, which was connected with the TGF-β/Smad pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Silibinin can have an important function across different stages of carcinogenesis, including inhibiting proliferation of cancer cells, regulating cell cycle and inducing apoptosis in order to play a considerable role in anti-tumor activity ( Bosch-Barrera and Menendez, 2015 ). Many studies have demonstrated that silibinin has promising anticancer effects across both androgen dependent and independent prostate, skin, bladder, lung, colon, breast and liver cancers ( Polachi et al, 2016 ; Vue et al, 2016 ; Barros et al, 2020 ; Liu Y et al, 2020 ). However, thus far, there have been no reports on the application of silibinin on cholangiocarcinoma treatment.…”
Section: Discussionmentioning
confidence: 99%